Graves' Disease and the Post-partum Period: An Intriguing Relationship - Croce, Laura; Di Dalmazi, Giulia; Orsolini, Francesca; Virili, Camilla; Brigante, Giulia; Gianetti, Elena; Moleti, Mariacarla; Napolitano, Giorgio; Tonacchera, Massimo; Rotondi, Mario (Frontiers in Endocrinology, 2019)
The post-partum period is an immunologically peculiar period in a woman's life. Indeed, most of the pregnancy-related immune changes gradually revert in the 12 months following delivery. Although the post-partum period has long been identified as a period of aggravation of autoimmune thyroid diseases, most of the currently available studies took into account the relationship between post-partum and autoimmune thyroiditis. More recently, the potential repercussions of the post-partum period on Graves' disease were also taken into account. The present mini review will briefly overview the most recent advances in our knowledge of the immunology of the post-partum period in relation with the potential repercussions on the clinical course of Graves' disease. Moreover, some peculiar aspects of post-partum Graves' disease in terms of clinical and biochemical presentation, diagnostic challenges, and specific therapeutic considerations also taking into account the recommendation of the latest clinical guidelines on the management of thyroid diseases in pregnancy will be overviewed.